Uma sequência didática sobre dilatação térmica com o uso de um experimento virtual - Rosendo Junior, José (2024)
The work presented in this dissertation aims to present a didactic sequence of teaching about thermal expansion, making use of a virtual experiment that simulates a laboratory practice of measuring the expansion of some materials, which can be manipulated in a way that is very similar to a real practice, carried out in physical laboratories. Initially, a historical description of the teaching of Physics in Brazil is made, and a bibliographic review regarding the thermal expansion and the thermal expansion coefficient, linear, superficial and volumetric, of the materials. Then, the importance of experimentation in helping the teaching of Physics and the benefits of using virtual experiments to overcome the lack of real physical laboratories is presented. In order to legitimize the proposal of didactic sequence presented in this work, a questionnaire was applied to the students of a 2nd year high school class, at the beginning of the didactic sequence and reapplied at the end of it, so that we verified an increase in the rate of correct resolution of the questionnaire by the students. In this way, the methodology presented here, of a didactic sequence using a virtual experiment, proves to be efficient in teaching thermal expansion, and can contribute to student learning.